Competition without fungibility: Evidence from alternative market structures for derivatives - Bartram, Söhnke M.; Fehle, Frank (Journal of Banking & Finance, 2007)
In this paper, we compare option contracts from a traditional derivatives exchange to bank-issued options, also referred to as covered warrants. While bank-issued option markets and traditional derivatives exchanges exhibit significant structural differences such as the absence of a central counterparty for bank-issued options, they frequently exist side-by-side, and the empirical evidence shows that there is significant overlap in their product offerings although options are not fungible between the two markets. The empirical analysis indicates that bid-ask spreads in either market are lowered by 1–2% due to competition from the other market, providing evidence that the benefits of competing market structures are available in the absence of fungibility.